Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\dfrac{2x+4}{2015}-\dfrac{2x+4}{2016}=\dfrac{2x+4}{2017}-\dfrac{2x+4}{2018}\)
\(\Rightarrow\left(2x+4\right)\left(\dfrac{1}{2015}-\dfrac{1}{2016}\right)=\left(2x+4\right)\left(\dfrac{1}{2017}-\dfrac{1}{2018}\right)\)
Vì \(\dfrac{1}{2015}-\dfrac{1}{2016}\ne\dfrac{1}{2016}-\dfrac{1}{2017}\) nên 2x + 4 = 0
\(\Rightarrow2x=-4\)
\(\Rightarrow x=-2\)
Vậy, x = -2
\(\dfrac{2x+4}{2015}-\dfrac{2x+4}{2016}=\dfrac{2x+4}{2017}-\dfrac{2x+4}{2018}\)
\(\Rightarrow\left(2x+4\right)\left(\dfrac{1}{2015}-\dfrac{1}{2016}\right)=\left(2x+4\right)\left(\dfrac{1}{2017}-\dfrac{1}{2018}\right)\)
Vì \(\dfrac{1}{2015}-\dfrac{1}{2016}\ne\dfrac{1}{2016}-\dfrac{1}{2017}\) nên \(2x+4=0\)
\(\Rightarrow2x=-4\)
\(\Rightarrow x=-2\)
Vậy, x = -2
\(a. 2x(3x^2-5x+3) = 6x^3-10x^2+6x \)
\(b. -2x(x^2+5x-3) = -2x^3-10x^2+6x\)
c. \(-\dfrac{1}{2}x^2\left(2x^3-4x+3\right)
=-x^5+2x^3-\dfrac{3}{2}x^2\)
\(d.\left(2x-1\right)\left(x^2+5-4\right)=\left(2x-1\right)\left(x^2+1\right)=2x^3+2x-x^2-1\)
e. \(-\left(5x-4\right)\left(2x+3\right)=10x^2+15x-8x-12=-10x^2+7x-12\)
f.\(\left(2x-y\right)\left(4x^2-2xy+y^2\right)=\left(2x-y\right)\left(2x-y\right)^2=\left(2x-y\right)^3\)
g.\(\left(3x-4\right)\left(x+4\right)+\left(5-x\right)\left(2x^2+3x-1\right)=3x^2+12x-4x-16+10x^2+15x-5-2x^3-3x^2+x=-2x^3+10x^2+24x-21\)
e. \(7x\left(x-4\right)-\left(7x+3\right)\left(2x^2-x+4\right)=7x^2-28x-14x^3+7x^2-28x-6x^2+3x+-12=-14x^3+8x^2-53x-12\)
\(=\dfrac{\left(x-2\right)\left(x+2\right)}{\left(x+1\right)^2}\cdot\dfrac{2\left(x+1\right)}{-2\left(x-2\right)}=\dfrac{-\left(x+2\right)}{x+1}\)
\(24x-4\left(2x-\frac{3}{4}\right)-4\left(3+\frac{2x}{2}\right)=36-3\left(x-\frac{3}{2}\right)-3\left(3-\frac{2x}{3}\right)\)
Đề như này đúng không bạn
Sửa đề:
\((2x^2+x-2015)^2+4(x^2-5x-2016)^2=4(2x^2+x-2015)(x^2-5x-2016)\)
\(\Rightarrow\left(2x^2+x-2015\right)^2-2.\left(2x^2+x-2015\right).2.\left(x^2-5x-2016\right)+[2.\left(x^2-5x-2016\right)]^2=0\)
\(\Rightarrow[2x^2+x-2015-2.\left(x^2-5x-2016\right)]^2=0\)
\(\Rightarrow11x+2017=0\)
\(\Rightarrow x=\frac{-2017}{11}\)
`Answer:`
\(\left|2x-4\right|+4=2x\Leftrightarrow\left|2x-4\right|=2x-4\)
`ĐK:|2x-4|>=0 =>2x-4>=0 =>2x>=4 =>x>=2`
\(\Leftrightarrow\orbr{\begin{cases}2x-4=2x-4\\2x-4=-\left(2x-4\right)\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}2x-4-2x=-4\\2x-4+2x=4\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}0-4=-4\\4x-4=4\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}-4=-4\left(\text{ Luôn đúng }\forall x\ge2\right)\\4x=4+4\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}-4=-4\left(\text{ Luôn đúng }\forall x\ge2\right)\\x=2\end{cases}}\)